THE PROBLEMS OF PROFESSIONAL PUBLIC ACCREDITATION OF ADDITIONAL PROFESSIONAL EDUCATION PROGRAMS AND THE PROSPECTS OF ITS IMPLEMENTATION - Tatyana V. Matveeva; Natalya V. Mashkova; Oksana N. Tkacheva; Olga G. Safina (Russian State Vocational Pedagogical University, 2015)
Leading role in the process of development and improvement of modern Russian education plays an additional professional education, which, to the greatest extent, responds to the qualitative changes in the socio-economic relations in a rapidly changing world. The aim of this paper is to identify the organizational and legal problems of professional and public accreditation of additional professional education programs in Russia and the opportunities development of this institution in modern conditions. The scientific research problem was to justify the need for professional and public accreditation of additional professional education programs of modern universities on the basis of delegation of procedures for evaluating the quality of education by public authorities to the public expert organizations, which ensure the independence and objectivity of the decisions made by qualified experts using a standardized assessment tools and tech to meet the needs of all parties concerned for highly qualified professionals. Methods. Empirical and theoretical methods were applied in the process of solving the problems in the scientific work to achieve the objectives of the study and test the hypothesis of an integrated methodology. Theoretical research methods involve: analysis of different literary sources (including legislative and regulatory enactments of the Higher Authorities of the Russian Federation, regulatory enactments of the Ministry of General and Vocational Education of the Russian Federation), compilation, synthesis of empirical data, comparative analysis, and others. Empirical research methods include: observation, testing, interview, questionnaire, ranking, pedagogical experiment, analysis of the products of activity, method of expert evaluations, methods of mathematical statistics, and other. Results. The expediency of independent accreditation procedures is proved. The goals that need to be solved to enhance the competitiveness of additional professional education objects in the new economic paradigm are indentified. Scientific novelty. The research findings include the following conclusions: the main tendencies in the development of accreditation procedures for assessing the quality of educational services in system of additional professional education in modern Russia are revealed; the fundamentals of professional public accreditation of additional professional education programs organization are justified; the gaps in the legal regulation of accreditation of additional educational programs are identified, and the necessity of professional public accreditation for improvement the competitiveness of additional educational programs is justified. Practical significance. Proposed and developed evaluation system of educational programs provides objectivity, credibility and transparency of the evaluation procedures; defines guidelines for accreditation institutions, expert committees, education authorities, managers and employees of educational institutions implementing programs of additional professional education. Systematic experience in evaluation of additional professional education institutions can be used in the career development system of senior executives.